Strategies Of Islamic Religious Education Teachers In Overcoming Students' Habit Of Swearing And Profanity (Study On Formal And Non-Formal Educational Institutions) - Farih Alfaaza, Muhammad; Nur Rofiuddin, Achmad; Darmawan, Didit (Journal of Islamic Elementary Education, 2025)
This study aims to find out the strategies of Islamic religious education teachers in overcoming students' habit of swearing and profanity in formal and non-formal educational institutions. This research uses a qualitative approach with phenomenological methods. Data collection techniques were carried out through in-depth interviews, observations, and documentation of Islamic religious education teachers and non-formal educators. The data analysis technique in this study uses phenomenological data analysis developed by Clark Moustakas. The results of the study show that the strategies applied by teachers include a persuasive approach, namely by giving advice with religious values, habituating commendable morals, educational sanctions, and examples from teachers. In addition, the role of the environment such as family and peers also affects the success of teachers in instilling moral values in students. This strategy has been proven to be able to minimize students' bad habits in speaking.